Propagation of SARS-CoV-2 in a Closed Cell Culture Device: Potential GMP Compatible Production Platform for Live-Attenuated Vaccine Candidates under BSL-3 Conditions? - Klessing, Stephan; Peter, Antonia Sophia; Fraedrich, Kirsten; Wagner, Jannik; Kummer, Mirko; Deutschmann, Janina; Steininger, Philipp; Steibl, Hans Dieter; Überla, Klaus (Viruses, 2023)
Live-attenuated SARS-CoV-2 vaccines present themselves as a promising approach for the induction of broad mucosal immunity. However, for initial safety assessment in clinical trials, virus production requires conditions meeting Good Manufacturing Practice (GMP) standards while maintaining biosafety level 3 (BSL-3) requirements. Since facilities providing the necessary complex ventilation systems to meet both requirements are rare, we here describe a possibility to reproducibly propagate SARS-CoV-2 in the automated, closed cell culture device CliniMACS Prodigy® in a common BSL-3 laboratory. In this proof-of-concept study, we observed an approximately 300-fold amplification of SARS-CoV-2 under serum-free conditions with high lot-to-lot consistency in the infectious titers obtained. With the possibility to increase production capacity to up to 3000 doses per run, this study outlines a potential fast-track approach for the production of live-attenuated vaccine candidates based on highly pathogenic viruses under GMP-like conditions that may contribute to pandemic preparedness.
CRIS-Team Scopus Importer:2023-03-10
Keywords: CliniMACS Prodigy®; GMP; human challenge study; live-attenuated vaccines; SARS-CoV-2; virus propagation